Pembuatan Alat Pembangkit Listrik Tenga Air (Plta) Mini Menggunakan Bahan Daur Ulang - Fajar Cahyadi; Ulinnuha Latifa (Jurnal Ilmiah Wahana Pendidikan, 2023)
Indonesia is a tropical country with two seasons-rainfall and drought. Moreover, Indonesia's geography always receives rainfall throughout the year, giving it a high rainfall of 2000-3000 mm per year. Water use as a source of energy has long been used to power hydroelectric (water plta). Hydroelectric plants tap into the potential energy and water-kinetic energy converged into angular power by water turbines. Water is also one of the most readily available sources of energy. Particularly in the west Java, it is seen at this time, as the season is already beginning. The use of hydroelectric power to meet the needs of electricity sources and, given the tiny new and renewable energy potential, would create hydroelectric power plants to optimize the use of new and renewable energy potential. In this article the authors will create a minuscule plant with easy materials so that the reader can build his own power plant without charging much money.